إعداد وحدة التعلم لمادة علم النفس التربوي لتعليم اللغة العربية في جامعة علي بن أبي طالب - nur cholis (Lughatu Ad-dhat, 2025)
An Arabic language teacher must at least equip themselves with three fields of knowledge: first, linguistics; second, educational science; and third, the psychology of Arabic language learning. The psychology of Arabic language learning helps the teacher to understand the students’ characteristics and identify the problems they face, enabling the teacher to provide appropriate solutions.The existence of a learning unit in the psychology of Arabic language learning as a source in university-level instruction is considered essential. This research is a development of a learning unit in the course “The Psychology of Arabic Language Learning.” The method used in this research is the Research and Development (R&D) approach based on the Borg and Gall model. The preparation of this unit involves five stages: 1) Needs analysis, 2) Preliminary design, 3) Unit design development, 4) Expert validation, 5) Revision. The results of expert evaluation are as follows: 1) Content evaluation: 85.25, 2) Accuracy evaluation: 84.22, 3) Presentation evaluation: 84.00The average score is 84.49, which indicates that the developed unit on the psychology of Arabic language learning is suitable for use in education. Keyword : learning Module, Psychologi Of Learning, Arabic Language Teaching